2018
DOI: 10.1194/jlr.m085332
|View full text |Cite
|
Sign up to set email alerts
|

A thumbwheel mechanism for APOA1 activation of LCAT activity in HDL[S]

Abstract: APOA1 is the most abundant protein in HDL. It modulates interactions that affect HDL's cardioprotective functions, in part via its activation of the enzyme, LCAT. On nascent discoidal HDL, APOA1 comprises 10 α-helical repeats arranged in an anti-parallel stacked-ring structure that encapsulates a lipid bilayer. Previous chemical cross-linking studies suggested that these APOA1 rings can adopt at least two different orientations, or registries, with respect to each other; however, the functional impact of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 63 publications
(64 reference statements)
4
74
0
2
Order By: Relevance
“…Treatment of hepatocytes with BPA increased~2.4-fold the activity of the construct (NF-κB) 3 -luc (p < 0.01), as presented in Figure 4B. As a control, we overexpressed IKKB or MEKK1 together with the construct (NF-κB) 3 -luc in HepG2 cells and we obtained an increase in the luciferase activity ( Figure 4B).…”
Section: The Mechanisms Of Apoa-i Downregulation By Bpamentioning
confidence: 77%
See 3 more Smart Citations
“…Treatment of hepatocytes with BPA increased~2.4-fold the activity of the construct (NF-κB) 3 -luc (p < 0.01), as presented in Figure 4B. As a control, we overexpressed IKKB or MEKK1 together with the construct (NF-κB) 3 -luc in HepG2 cells and we obtained an increase in the luciferase activity ( Figure 4B).…”
Section: The Mechanisms Of Apoa-i Downregulation By Bpamentioning
confidence: 77%
“…In parallel, we assessed the capacity of BPA to activate a promoter containing NF-κB binding sites ( Figure 4B). For this purpose, we transiently transfected hepatocytes with the construct (NF-κB) 3 -luc containing three copies of the NF-κB binding site cloned upstream of the minimal SV40 promoter and the luciferase reporter gene in pGL2-Promoter Vector (Promega). Treatment of hepatocytes with BPA increased~2.4-fold the activity of the construct (NF-κB) 3 -luc (p < 0.01), as presented in Figure 4B.…”
Section: The Mechanisms Of Apoa-i Downregulation By Bpamentioning
confidence: 99%
See 2 more Smart Citations
“…Another key member of the apolipoprotein family is ApoA1 which is the major protein constituent of plasma HDL. In addition to high expression in several peripheral tissues including the liver and intestine, ApoA1 is also one of the most abundant apolipoproteins in CSF(cerebrospinal fluid) (Roheim et al, 1979, Harr et al, 1996 and also serves as an important cofactor on LCAT activation (Sorci-Thomas et al, 2009, Cooke et al, 2018. Indeed, our data indicated that ApoA1 is far more abundant than ApoA4 in the murine brain (emPAI value 33.8±13.1) while still displaying a high level of heavy labelling by pSIVOM analysis (average heavy/light abundance ratio 16.9±1.5).…”
Section: Discussionmentioning
confidence: 99%